Implementasi Algoritma Boldi Vigna Kompresi File Teks - Dini Novelia (Jurnal Ilmu Komputer, Teknologi Dan Informasi, 2025)
Data compression technology is the process of converting a set of data into a lower form of code. Compression techniques are usually used for data transmission processes, Data compression or data compression is a way in computer science to require smaller storage space, making it more efficient in storage. Boldi Vigna is an example of an algorithm for compression where both compress data by descending sorting each character. Implementation is the application or implementation, as an action to carry out the plans that have been made.